2006
DOI: 10.1211/jpp.58.5.0016
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of rutin, a bioflavonoid, on lipid peroxides and antioxidants in isoproterenol-induced myocardial infarction in rats

Abstract: The consumption of diets rich in plant foods is associated with a reduced risk of cardiovascular diseases. This study aimed to evaluate the preventive role of rutin on lipid peroxides and antioxidants in normal and isoproterenol-induced myocardial infarction in rats. Subcutaneous injection of isoproterenol (150 mg kg(-1)) to male Wistar rats at an interval of 24 h for two days showed a significant increase in the activity of serum cardiac marker enzymes (creatine kinase, lactate dehydrogenase, aspartate transa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 30 publications
(25 reference statements)
4
53
1
Order By: Relevance
“…There was a significant elevation in serum CK-MB confirming the acute myocardial infarction in rats. These observations were in line with previous studies conducted on rats treated with iso (26). CK-MB is localized predominantly in the heart, and this makes it a valuable diagnostic marker for MI, as damages specific to the myocardium would result in the elevation of serum CK-MB levels (10,11,27).…”
Section: Discussionsupporting
confidence: 91%
“…There was a significant elevation in serum CK-MB confirming the acute myocardial infarction in rats. These observations were in line with previous studies conducted on rats treated with iso (26). CK-MB is localized predominantly in the heart, and this makes it a valuable diagnostic marker for MI, as damages specific to the myocardium would result in the elevation of serum CK-MB levels (10,11,27).…”
Section: Discussionsupporting
confidence: 91%
“…Normal control and ISO control rats were received CMC alone (1 ml/rat). Rutin pretreatment and dosage fixation was based on our earlier study [9]. Twelve hours after the second dose of ISO injection (on 45th day), all the rats were anesthetized and then killed by cervical decapitation.…”
Section: Experimental Designmentioning
confidence: 99%
“…A wide variety of pharmacological actions of rutin were reported-antibacterial, anti-tumor, anti-inflammatory, anti-diarrheal, antiulcer, anti-mutagenic, vasodilator, immunomodulatory and hepatoprotective [7]. Previously, we reported the preventive effects of rutin on lipids, lipoproteins, ATPases, lipid peroxides and antioxidants in ISO-induced rats [8,9].…”
Section: Introductionmentioning
confidence: 98%
“…37 Although this rat model does not exactly reflect the clinical situation in terms of coronary occlusion and regional MI, animals develop "infarct-like" lesions when injected with isoproterenol. In a rabbit model of coronary artery ligation, Krieg et al 38 recently showed that cinaciguat elicited an infarct-reducing effect.…”
Section: Study Limitationsmentioning
confidence: 99%